Coating powder with high light stability

By combining metal oxides with multifunctional coating components, a coating powder with a high-weight load dispersion solution is formed, which solves the problem of metal oxides forming free radicals under ultraviolet light irradiation, realizes the chemical and light stability of the compound, and extends the effective period of the antioxidant.

JP7649568B2Active Publication Date: 2025-03-21NANOPHASE TECHNOLOGIES CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023171088
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-04-10
Filing Date
2023-10-02
Publication Date
2025-03-21
Estimated Expiration
2038-04-10

AI Technical Summary

Technical Problem

In the prior art, metal oxides such as zinc oxide and titanium oxide have photocatalytic behavior under ultraviolet light irradiation, forming free radicals, resulting in unstability of compound and skin allergies, and antioxidants are prone to oxidation failure under ultraviolet light irradiation.

Method used

Using multifunctional coating powder, a coating powder with chemical stability, light stability and low viscosity is formed by combining zinc oxide or other metal oxide with multifunctional coating components such as polydimethylsiloxane.

Benefits of technology

It improves the light stability of metal oxides, reduces the formation of free radicals, extends the validity period of antioxidants, and enhances the stability and safety of compounds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649568000023
    Figure 0007649568000023
  • Figure 0007649568000024
    Figure 0007649568000024
  • Figure 0007649568000001
    Figure 0007649568000001
Patent Text Reader

Abstract

To provide a coated powder having high photostability, a dispersion liquid and a composition including the coated powder, and a method for producing the coated powder.SOLUTION: A coated powder comprises (a) particles, and (b) a coating on the surface of the particles including (1) silica moieties, (2) organo oxysilane moieties selected from the group consisting of mono-organo oxysilane moieties, bi-organo oxysilane moieties and tri-organo oxysilane moieties, and (3) poly(dialkyl)siloxane moieties. The amount by weight in SiO2 equivalents of the organo oxysilane moieties and the silica moieties is at least 0.0625% of the total coated powder weight per m2 / g of the specific surface area of the particle to be coated.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [Background technology] Particles are added to enhance and modify the properties of many different types of compositions and products. Examples include ultraviolet (UV) light absorbing particles, pigments, colorants, fillers, matting agents, light scattering particles, abrasion resistant particles, viscosity modifiers, magnetic particles, and reflective particles.

[0002] Particles containing oxides are particularly suitable as additives, especially those containing zinc oxide, titanium oxide, silicon oxide, aluminum oxide, iron oxide and / or rare earth metal oxide. These oxides are thermodynamically stable, typically cannot react with oxygen, which is widely distributed in the environment, and tend to be less reactive with water than many other oxide and non-oxide materials. These oxide materials have been used as pigments and abrasives for centuries.

[0003] Particles made of certain metal oxides, most notably titanium dioxide, are of particular interest because they are usually colorless and transparent to visible light and offer protection against exposure to UV light; however, due to the photocatalytic behavior of these oxides, they tend to be poorly photostable. Metal oxides exposed to UV radiation result in an increase in free radicals. These free radicals can lead to the destabilization of the formulation itself. In addition, free radicals can lead to the formation of hydroperoxides and other peroxidic free radicals, which are known to induce contact dermatitis and severe allergic reactions. These free radicals can also trigger chain reactions resulting in reactive oxygen species (ROS). These highly reactive derivatives react with cellular components, including lipid membranes, and are believed to be responsible for photoaging and skin cancer that appear later in life. ROS deplete and damage nonenzymatic and enzymatic antioxidant defense systems, causing permanent genetic damage. Other components in cosmetic compositions also have low photostability and can generate additional free radicals on the skin surface.

[0004] It has been found that coating the particles improves the photostability of the particles. The coated powders are used to prepare cosmetic compositions for application to the skin, such as compositions for protecting the skin from UV radiation (e.g. sunscreens).

[0005] Particles can be coated to produce coated powders that have chemical stability, light stability, and the ability to form dispersions with high weight loadings and low viscosity. For example, coatings that produce chemical stability and light stability have been found, and such coated particles can be used to form dispersions with high weight loadings and low viscosity. The coatings include (1) silica moieties, (2) organooxysilane moieties selected from the group consisting of mono-organooxysilane moieties, bi-organooxysilane moieties, and tri-organooxysilane moieties, and (3) poly(dialkyl)siloxane moieties. See, for example, U.S. Pat. No. 9,139,737.

[0006] Antioxidants are often used in cosmetic skin care products, and lose their effectiveness through oxidation process under UV radiation.Addition of coating powder that blocks and absorbs UV radiation can reduce the oxidation of antioxidants caused by UV radiation.However, many UV blocking particles such as zinc oxide and titanium oxide show photocatalytic activity, which can lead to the generation of peroxide free radicals in cosmetic compositions.This can cause the stability and effectiveness of antioxidants to be impaired due to the immediate reaction between antioxidants and free radicals or the products generated by free radicals. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] U.S. Pat. No. 9,139,737 Summary of the Invention [Means for solving the problem]

[0008] In a first aspect, the invention is a coated powder comprising: (a) a particle; and (b) a coating on the surface of the particle, the coating comprising: (1) a silica portion; (2) an organooxysilane portion selected from the group consisting of a mono-organooxysilane portion, a bi-organooxysilane portion, and a tri-organooxysilane portion; and (3) a poly(dialkyl)siloxane portion. The amount of organooxysilane portion and silica portion by weight in terms of SiO2 equivalent is preferably less than m2 of the specific surface area of ​​the particle to be coated. 2 / g of the total weight of the coating powder.

[0009] In a second aspect, the invention is a dispersion that includes (1) a coating powder, (2) a fluid, and (3) an antioxidant.

[0010] In a third aspect, the present invention provides a method for producing a coating powder, comprising: (i) particles; (ii) a first alkoxysilane selected from the group consisting of tetra-alkoxysilanes, poly(tetra-alkoxysilanes), and mixtures thereof; (iii) a mono-organoalkoxysilane; A method of producing a particle, comprising coating the particle with a polymer by polymerizing a composition comprising an organoalkoxysilane selected from the group consisting of bi-organoalkoxysilanes, tri-organoalkoxysilanes, and mixtures thereof, and (iv) a second alkoxysilane selected from the group consisting of poly(dialkyl)siloxanes, and mixtures thereof, wherein the amount by weight of the SiO2 equivalent of the organooxysilane portion and the silica portion is at least 0.0625% of the total weight of the coated powder per m2 / g of the specific surface area of ​​the particle to be coated.

[0011] In a fourth aspect, the invention is a coating powder that is ultra-photostable.

[0012] In a fifth aspect, the invention is a method of protecting skin from light comprising coating the skin with a composition comprising a coating powder.

[0013] In a sixth aspect, the invention is a method of protecting keratinous material comprising coating the keratinous material with a composition comprising a coating powder.

[0014] In a seventh aspect, the invention is a method of protecting skin from light comprising covering the skin with a dispersion.

[0015] In an eighth aspect, the invention is a method of inhibiting lipid peroxidation comprising applying to skin a composition comprising a coating powder.

[0016] In a ninth aspect, the invention is a method of preventing or reducing fine lines and wrinkles on the skin comprising applying to the skin a composition comprising a coating powder.

[0017] In a tenth aspect, the invention is a method of preventing loss of elasticity in skin comprising applying to the skin a composition comprising a coating powder.

[0018] In an eleventh aspect, the invention is a method of preventing skin thinning comprising applying to the skin a composition comprising a coating powder.

[0019] definition The term "nanoparticles" refers to particles having a diameter of up to 999 nm. Nanoparticles preferably have a diameter of 10 nm to 500 nm.

[0020] The term "microparticle" refers to a particle having a diameter between 1 μm and 100 μm.

[0021] The term "particle size" means, unless otherwise specified, the average diameter of an image of a particle when viewed under an electron microscope. The term "average particle size" means the average particle size of a population of particles.

[0022] "High solids content" or "high weight loading" means that the referenced composition has at least 50% by weight of solid particles.

[0023] "Alkyl" (or alkyl- or alky-) refers to a substituted or unsubstituted, straight, branched or cyclic hydrocarbon chain, preferably containing 1 to 22 carbon atoms. More preferred alkyl groups are lower alkyl groups, such as, for example, alkyl groups containing 1 to 10 carbon atoms. Preferred cycloalkyls have 3 to 10, preferably 3 to 6, carbon atoms in their ring structure. Suitable examples of unsubstituted alkyl groups include methyl, ethyl, propyl, isopropyl, cyclopropyl, butyl, iso-butyl, tert-butyl, sec-butyl, cyclobutyl, pentyl, cyclopentyl, hexyl, and cyclohexyl.

[0024] "Alkenyl" refers to a substituted or unsubstituted, linear, branched or cyclic, unsaturated hydrocarbon chain containing at least one double bond, preferably having 2 to 22, more preferably 2 to 6 carbon atoms. Exemplary unsubstituted alkenyl groups include ethenyl (or vinyl) (-CH=CH2), 1-propenyl, 2-propenyl (or allyl) (-CH2-CH=CH2), 1,3-butadienyl (-CH=CHCH=CH2), 1-butenyl (-CH=CHCH2CH3), hexenyl, pentenyl, and 1,3,5-hexatrienyl. Preferred cycloalkenyl groups contain 5 to 8 carbon atoms and at least one double bond. Examples of cycloalkenyl groups include cyclohexadienyl, cyclohexenyl, cyclopentenyl, cycloheptenyl, cyclooctenyl, cyclohexadienyl, cycloheptadienyl, and cyclooctatrienyl.

[0025] "Alkynyl" refers to a substituted or unsubstituted, straight, branched or cyclic, unsaturated hydrocarbon chain containing at least one triple bond, preferably having 2 to 22, more preferably 2 to 6 carbon atoms.

[0026] "Aryl" refers to any aromatic carbocyclic or heterocyclic group, preferably having from 3 to 10 carbon atoms. Aryl groups can be cyclic (such as phenyl (or Ph)) or polycyclic (such as naphthyl) and can be unsubstituted or substituted. Preferred aryl groups include phenyl, naphthyl, furyl, thienyl, pyridyl, indolyl, quinolinyl, or isoquinolinyl.

[0027] A "heterocyclic radical" refers to a stable, saturated, partially unsaturated, or aromatic ring, preferably containing 5 to 10 atoms, more preferably 5 or 6 atoms. The ring may be substituted one or more times (preferably 1, 2, 3, 4, or 5 times) with a substituent. The ring may be mono-, bi-, or polycyclic. A heterocyclic group consists of carbon atoms and one to three heteroatoms independently selected from the group consisting of nitrogen, oxygen, and sulfur. The heteroatoms may be protected or unprotected. Examples of useful heterocyclic groups include substituted or unsubstituted acridine, benzathiazolin, benzimidazole, benzofuran, benzothiophene, benzthiazole, benzothiophenyl, carbazole, cinnoline, furan, imidazole, benzothiophene ... Examples of suitable aryl amines include aryl, 1H-indazole, indole, isoindole, isoquinoline, isothiazole, morpholine, oxazole, phenazine, phenothiazine, phenoxazine, phthalazine, piperazine, pteridine, purine, pyrazine, pyrazole, pyridazine, pyridine, pyrimidine, pyrrole, quinazoline, quinoline, quinoxaline, thiazole, 1,3,4-thiadiazole, thiophene, 1,3,5-triazine, and triazole.

[0028] By "substituted" it is meant that the moiety contains at least one substituent, preferably 1 to 3. Suitable substituents include hydrogen (H) and hydroxyl (-OH), amino (-NH2), oxy (-O-), carbonyl (-CO-), thiol, alkyl, alkenyl, alkynyl, alkoxy, halo, nitrile, nitro, aryl, and heterocyclic groups.

[0029] The photostability of titanium dioxide (TiO2) is measured using the test described below. This test is designated "TiO2 photostability test". First, a stock solution of 25% resorcinol in ethanol is prepared. 8.9 g (±0.01 g) of Finsolv TN and 0.1 g (±0.005 g) of Hostaphat KW 340D are placed in a glass scintillation vial. Next, Heat the capped vial until the Hostaphat KW 340D has dissolved and the solution is homogenous (approximately 15 minutes). Place in a 50°C oven for 15 minutes. After removing the vial from the oven, add 1.0g (±0.01g) of coated titanium dioxide powder to the solution. Place the solution in a sonication bath and sonicate for 15 minutes. Add 1.0g (±0.01g) of 25% resorcinol in ethanol from the first step to the scintillation vial and mix thoroughly by hand until homogenous. Fill a quartz cuvette with the mixture and cap with a Teflon lid. Then, use a Milton Roy Color Mate Colorimeter or a suitable equivalent colorimeter to measure the color of the above sample. Test the mixture. Prior to testing the above mixture, calibrate the colorimeter using the white tile calibration standard. After recording the results of the "pre-irradiated sample," place the cuvette containing the sample in the QUV The mixture was then placed in a Q-Labs QUV Weatherometer using a UVB bulb at 1.23 Watts. -2 seconds -1 The mixture is then removed for immediate color measurement with a colorimeter. Light stability can be expressed as the total color change compared to a standard for a stated UV exposure time (L * a * b * ΔE in color space). ΔE is calculated according to the CIE76 definition from the following formula:

[0030]

number

[0031] During the ceremony,

[0032] [ka]

[0033] are the color coordinates of the test mixture after irradiation,

[0034] [ka]

[0035] =99.47,

[0036] [ka]

[0037] =-0.16, and

[0038] [ka]

[0039] =-0.17, which corresponds to the color coordinates of the white control tile. The coated TiO2 particles are "ultra-photostable" if they have a ΔE of 15 or less in the photostability test described above.

[0040] The following test can be used to test the photostability of major components other than TiO2, such as zinc oxide (ZnO). This test is designated as the "DPPH photostability test." First, 0.025 g ± 0.001 g of coated ZnO powder is placed into four 50 mL disposable plastic beakers. 0.0125% DPPH (di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium, also designated as diphenylpicrylhydrazyl; CAS number 1898-66-4) is prepared in BCS (ethylene glycol butyl ether) solution. BC Add 19.975 g ± 0.001 of the 0.0125% DPPH in S solution to each beaker containing the coating powder. Mix this thoroughly with a glass stirring rod and sonicate each beaker for 20 seconds to ensure good dispersion of the powder throughout the solution. After sonication, transfer the samples to labeled scintillation vials. Measure the pre-irradiated samples on a calibrated Milton Roy Color Mate Colorimeter or suitable equivalent colorimeter. After the measurements are taken, transfer the samples to a calibrated Milton Roy Color Mate Colorimeter or suitable equivalent colorimeter. The test mixtures are then irradiated in a Q-Labs QUV Weatherometer using a UVA or UVB bulb at 0.35 Wm -2 seconds -1 The samples are exposed to UV light for exactly 10 minutes using a constant temperature of 50°C at 200°C. The UVA bulbs are used to test particles that filter UVA radiation, and the UVB bulbs are used to test particles that filter UVB radiation. Finally, after irradiation the samples are measured with a colorimeter. In this case, the photostability after UV exposure is indicated by the persistence of the purple color due to the dye's absorption band at 520 nm. The photostability can be expressed as the total color change compared to a standard for the stated UV exposure time (L * a * b * ΔE in color space). ΔE is calculated according to the CIE76 definition from the following formula:

[0041]

number

[0042] During the ceremony,

[0043] [ka]

[0044] are the color coordinates of the test mixture after irradiation, and

[0045] [ka]

[0046] are the initial color coordinates of the test mixture before irradiation. Data are reported as the average ΔE value of four samples. Coated particles are "ultra-photostable" if they have a ΔE of 4.5 or less in the photostability test described above.

[0047] The light stability of coated effect pigments is measured using a modified version of the aforementioned test. This test is designated "Effect Pigment Light Stability Test". The modification was necessary to remove noise in the colorimetric measurement induced by the reflectance of the interference pigment itself in the sample. The test is described below. 0.0125% DPPH (Di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium, also designated diphenylpicrylhydrazyl; CAS number 1898-66-4) is prepared in BCS (ethylene glycol butyl ether) solution. 20 ml Transfer an aliquot of the DPPH solution to a labeled scintillation vial. Measure the sample in a calibrated MiltonRoy Color Mate Colorimeter or a suitable equivalent colorimeter. Next, 0.025g ± 0.001g of the coated effect pigment powder is placed into four 50mL disposable plastic beakers. 19.975g ± 0.001 of the 0.0125% DPPH in BCS solution is added to each beaker containing the coated powder. This is mixed thoroughly with a glass stirring rod and each beaker is sonicated for 20 seconds to ensure good dispersion of the powder throughout the solution. After sonication, each sample is transferred to a labeled scintillation vial. The test mixtures are then placed in a Q-Labs QUV Weather-O-Meter with a UVB bulb at 0.35Wm. -2 seconds -1The dye is exposed to UV light for exactly 10 minutes using a constant temperature of 50°C at 25°C. The irradiated samples are then filtered through an appropriate 1 μm filter to remove effect pigments that may interfere with the color measurement. Finally, the filtered irradiated samples are measured in a colorimeter. As mentioned before, the photostability after UV exposure is indicated by the persistence of the purple color due to the dye's absorption band at 520 nm. The photostability can be expressed as the total color change compared to a standard for the stated UV exposure time (L * a * b * ΔE in color space). ΔE is calculated according to the CIE76 definition from the following formula:

[0048]

number

[0049] During the ceremony,

[0050] [ka]

[0051] are the color coordinates of the test mixture after irradiation, and

[0052] [ka]

[0053] are the initial color coordinates of the as-prepared DPPH solution. Data are reported as the average ΔE value of four samples. Coated particles are "super photostable" if they have a ΔE of 1.15 or less in the photostability test described above, which represents half of the just noticeable difference value accepted according to CIE 76.

[0054] Chemical reactivity is measured using the following chemical reactivity test: A 20 g glass vial is filled with 4.5 g of a stock solution of 5% n-propyl gallate (propyl 3,4,5-trihydroxybenzoate, Aldrich) in isopropyl alcohol. One-half of the grams of the powder is placed in a glass vial. The glass vial is then vigorously agitated for 30 seconds, such as by placing in a bath sonicator. The mixture is allowed to sit for 30 minutes. The sample is then gently mixed using a pipette and transferred to a cuvette (polycarbonate, polystyrene, or glass) with a 1 cm path length. The total color change (ΔE) is then measured using a DataColor-International Spectraflash SF3000 colorimeter against a factory white color standard. Chemical reactivity is expressed as total color change (ΔE). A powder is considered chemically reactive upon application if the chemical reactivity test results in a tan brown appearance with a ΔE value greater than 20.

[0055] Hydrophobicity was determined using the following hydrophobicity test (the visible water floatation test commonly used in the cosmetics industry and described in U.S. Pat. No. 4,454,288). The hydrophobicity test is performed using a hydrophobicity tester (described in US Pat. No. 8). Approximately 30 ml of deionized water is placed in a glass jar. Approximately 3.0 g ± 0.30 g of powder to be tested is added to the glass jar. The glass jar is tightly sealed and the sample is swirled 4-5 times and vigorously shaken 4-5 times to achieve intimate contact between the water and the powder. If the powder is buoyant (floats on the surface of the water) and the water is clear after 15 minutes, the powder is considered to be hydrophobic. If the powder is not buoyant and the water is clear after 15 minutes, or if the powder is buoyant but the water is not clear after 15 minutes, the sample is slightly hydrophobic.

[0056] The flowability of a powder dispersion was evaluated using the following run-off distance test: The dispersion liquid was ethylhexyl benzoate (Finsolv® EB, manufactured by Innospec). ) at 50% solids. Three drops (75 mg) of the dispersion are placed from a pipette onto a clean glass plate substrate while the surface is horizontal. The glass plate substrate is then held vertically at a 90° angle for 120 seconds, allowing the dispersion to flow. The flowability of the dispersion is expressed as the distance the dispersion flows from the origin. (This test was only used during the initial screening; a flow distance of 164 ± 10 mm (reported as standard error) measured from the origin was 0.01 mm after 20 seconds.) -1 (corresponding to a viscosity of 145±25 cP (reported as standard error) at a shear rate of 1. A coated powder is considered to produce a pourable dispersion if it exhibits a runoff distance of greater than 100 mm in a 50% solids dispersion in ethylhexyl benzoate.

[0057] The viscosity of the powder dispersion is measured using the following viscosity test: The powder dispersion is made of capric / caprylic triglyceride (ALDO® MCT Special KFG, Lonza, CAS number 73398-61-5), ethylhexyl benzoate (Finsolv® EB, Innospec). ), and linear alkyl benzoates (Finsolv® TN C 12-15 Alkyl Benzoate C Viscosity is measured for each dispersion at 25° C. using a Brookfield DVIII+ Ultra Rheometer equipped with a CP52 spindle. Measurements are taken at 0.1 s. -1 ~100 seconds -1 The shear rate is in the range of 100-200 / s.

[0058] The specific surface area of ​​the particle is m 2 / g and determined using the Brunauer-Emmett-Teller (BET) method.

[0059] By SiO2 equivalent is meant the weight of SiO2 present after all silicon in the coating is converted to SiO2. For example, the "weight amount of SiO2 equivalent" of a part means that all silicon forming the coating is converted to SiO2 and measured to determine the percentage of each part in the coating powder.

[0060] Antioxidative power (AP) is measured using the AP method developed by Gematria Laboratories (Berlin, DE), which measures the overall antioxidant power of active ingredients, i.e. plant extracts, vitamins, etc., by observing their reducing activity towards a stable test radical -DPPH, using Electron Spin Resonance (ESR) spectroscopy. The AP method utilizes the well-known DPPH method, with the main difference being that it uses both antioxidant capacity and antioxidant activity to characterize the antioxidants tested. For this purpose, different concentrations of the active ingredient are analyzed in real time by ESR spectroscopy, tracking the decrease in the test radical spin at each setting. With this innovative technique, important kinetic information is additionally obtained that is completely left out by most other test systems. Thus, both the reaction time and the reduction potential of the antioxidant contribute to the calculation of AP. AP = (RA × N spins) / (w c ×t r )

[0061] AP can be expressed by the above formula, where RA is the constant reduction amplitude (1 / e 2 ), Nspin is the amount of reduced free radical characterized by the free electrons (spin) of DPPH, and w c is the characteristic weight of the antioxidant product, and t ris the reduction time (Jung K, Richter J, Kabrodt K, Lucke IM, Schellenberg I, Herrling T. The antioxidant power AP--A new quantitative time dependent (2D) parameter for the determination of the antioxidant capacity and reactivity of different plants. Spectrochim Acta A Mol BiomolSpectrosc. 63(2006):846-50 The AP obtained is expressed in antioxidant units (AU), with 1AU being corresponds to the activity of a 1 ppm solution of pure vitamin C (ascorbic acid) as a benchmark. This method allows for a rapid and generally applicable technique for the measurement of AP across a wide range of different classes of substances. [Brief description of the drawings]

[0062] [Figure 1] 1 is a graph of the relative percentage of free radicals with varying UV exposure time. [Diagram 2] 1 is a graph of relative AP values ​​for various antioxidants after UV exposure when combined with either ZnO with an octyltriethyloxysilane coating or ZnO with a multifunctional coating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0063] Coating powders of TiO2 and other selected metal oxides are desirable for use in UV-protective topical skin compositions and other UV-protective coatings.However, to be commercially desirable, such coating powders must be (a) photostable, so that they do not change color significantly during exposure to UV light; (b) not chemically reactive, so that they do not react with or discolor the composition during storage; and (c) capable of being formed into high weight-loading dispersions that allow high SPF values ​​with minimal introduction of carrier fluids and for cost-effective shipping and storage, but have low enough viscosity to be easily processed and mixed when preparing consumer compositions.

[0064] The multifunctional coating powder and high dispersion solids described in U.S. Patent No. 9,139,737 are a significant improvement over other existing coating powders, but can be further improved by increasing the light stability of the coating powder. Furthermore, adding an antioxidant to the UV protection composition reduces the amount of induced free radicals caused by UV radiation exposure.

[0065] The present application utilizes coating powders that have excellent light stability in addition to being chemically stable and capable of being formed into dispersions at high weight loadings. The coating powders are ultra-light stable. The coating powders can be used to form compositions containing antioxidants, reducing the loss of antioxidants upon exposure to light.

[0066] The coated powders are particles coated with a polymer and are prepared by polymerizing a composition containing particles and at least three components: (A) a first alkoxysilane selected from the group consisting of tetra-alkoxysilanes, poly(tetra-alkoxysilanes), and mixtures thereof, (B) an organoalkoxysilane selected from the group consisting of mono-organoalkoxysilanes, bi-organoalkoxysilanes, tri-organoalkoxysilanes, and mixtures thereof, and (C) a second alkoxysilane selected from the group consisting of poly(dialkyl)siloxanes, and mixtures thereof.

[0067] The coating formed contains three components: (A) a silica portion, (B) an organooxysilane portion selected from the group consisting of a mono-organooxysilane portion, a bi-organooxysilane portion, and a tri-organooxysilane portion, and (C) a portion corresponding to each of the poly(dialkyl)siloxane portions. The coating powder can be used to form a dispersion in a cosmetically acceptable fluid having a high solids content and low viscosity.

[0068] It has been found that when at least a certain amount of Si (measured as SiO2 weight equivalent) from all silanes is present in the coating, it results in excellent photostability. The composition ranges for each component are based on SiO2 equivalent. The SiO2 from all silane moieties, i.e., silica moieties and organooxysilane moieties, accounts for approximately 1 / 2 m of the specific surface area of ​​the coated particle. 2 / g must be greater than or equal to 0.0625% of the total weight of the coated powder. The silane moieties can be mono-, di-, tri-, and tetra-functional.

[0069] The coating powders can be used to form dispersions in fluids with high solids and low viscosity. The dispersions can be used to prepare cosmetic compositions for application to the skin, such as compositions for protecting the skin from UV radiation (e.g., sunscreens). Materials considered cosmetically acceptable are those listed in the International Nomenclature of Cosmetic Ingredients (INCI). Examples of cosmetically acceptable fluids are ethylhexyl benzoate (EB), linear alkyl benzoates (L), and alkyl benzoates (ALK). AB (linear alkyl benzoate), caprylic / capric triglyceride (CCT), squalane, natural oils, and various silicone fluids. Naturally occurring oils are oils derived from seeds, legumes, fruits, flowers, skins, leaves, etc., including derivatives thereof. Examples of naturally occurring oils are olive oil and soybean oil.

[0070] The coating powders, as well as dispersions of the coating powders, can be used in various products. They can be added to dermatological compositions to provide UV protection to the skin, especially in the case of TiO2- and ZnO-containing coating powders; the coating powders can also be added to such compositions as inorganic pigments. The coating powders can also be added to shampoos, lotions, gels, hairsprays, aerosol foaming creams or milks to cleanse, color and style the hair, while also providing UV protection to the hair. The coating powders can be added to paints, sealants and other coatings for wood, plastics and other building materials; in the case of TiO2- and ZnO-containing coating powders, UV protection is also provided. The coating powders can also be added to resins, filled polymers and plastics, and inks. Magnetic fluids can be prepared when the metal oxide is magnetic, as in the case of certain iron oxides and rare earth oxides.

[0071] The particles are preferably, for example, zinc oxide, titanium oxide, silicon oxide, aluminum oxide. Metal oxides such as iron oxide, bismuth oxide, cerium oxide, rare earth oxides, infrared absorbing binary and ternary mixed metal oxides, and mixtures thereof. Examples include ZnO, TiO2, SiO2, Al2O3, Fe2O3, CeO2, SnO2, zirconium-cerium oxide, mixed zirconium-rare earth oxides containing cerium, aluminosilicates (including amorphous aluminosilicates, crystalline aluminosilicates, and pumice) and other silicates, alumina, aluminosilicates, aluminum oxides including magnesium aluminum oxide (e.g., spinels), zinc oxides doped with trivalent metal cations (including aluminum-doped ZnO), antimony-tin oxide (ATO), indium-tin oxide (ITO), fluorine-doped tin oxide and doped tin oxide. Examples of ceramic compositions that may be used include tungsten oxide, which has been oxidized with tungsten oxide. Mineral oxides such as mica and natural mineral oxides may also be used. Other ceramic compositions including metals, carbides and nitrides and mixtures thereof, as well as mixtures with oxides, may also be used.

[0072] The particles may be effect pigments. Effect pigments are typically platelet or plate-like pigment particles coated with a thin layer of a secondary material having a higher refractive index. The composition of the underlying platelets is typically mica, synthetic mica, silica, or alumina. The coating is typically titanium dioxide (typically in anatase form), iron oxide, or bismuth oxychloride. The color of the pigment is controlled by the thickness of the coating layer. Effect pigments typically range in size from 1 to 100 μm. Pigments are also referred to as pearlescent pigments and interference pigments. These materials are commercially available (XIRALLIC®, PYRISMA®, COLORSTREAM® and IRIODIN® product lines from EMD Performance Materials, MEARLIN® pearlescent pigments from BASF, and SYNCRYSTAL® from Eckart). , SYNAFIL®, MIRAGE®, and VISIONAIRE® effect pigments) .

[0073] Preferably, the particles have a particle size of up to 999 nm, including particle sizes of up to 100, 200, and 500 nm, more preferably a particle size of 10 nm to 500 nm, most preferably a particle size of 15 nm to 250 nm, such as 20, 30, 40, 50, 60, 70, 80, 90, and 100 nm. Preferably, the particles have an average particle size of up to 999 nm, including average particle sizes of up to 100, 200, and 500 nm, more preferably an average particle size of 10 nm to 500 nm, most preferably an average particle size of 15 nm to 250 nm, such as 20, 30, 40, 50, 60, 70, 80, 90, and 100 nm. Alternatively, the particles may have a particle size of 1 μm to 100 μm. Preferably, the particles have an average size of 1 to 10 μm.

[0074] The particles may be coated, preferably without a solvent, by polymerizing the composition, with at least a portion of the composition in the gas phase, comprising (A) a first alkoxysilane selected from the group consisting of tetra-alkoxysilanes, poly(tetra-alkoxysilanes), and mixtures thereof, (B) an organoalkoxysilane selected from the group consisting of mono-organoalkoxysilanes, bi-organoalkoxysilanes, tri-organoalkoxysilanes, and mixtures thereof, and (C) a second alkoxysilane selected from the group consisting of poly(dialkyl)siloxanes, and mixtures thereof.

[0075] Preferably, the first alkoxysilane is present in an amount of 0.1-8% by weight of the coated powder, more preferably 0.5%-7% by weight of the coated powder, and most preferably 1.0-5% by weight, including 1.5, 2, 2.5, 3, 3.5, 4, and 4.5% by weight of the coated powder. Preferably, the organoalkoxysilane is present in an amount of 0.01-5% by weight of the coated particle, more preferably 0.05-3% by weight of the coated powder, and most preferably 0.1-1% by weight, including 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, and 0.9% by weight of the coated powder. Preferably, the second alkoxysilane is present in an amount of 0.1-10% by weight of the coated powder, more preferably 0.5%-5% by weight of the coated powder, and most preferably 1.0, 1.25, 1.5, 1.75, 1.85, 1.95, 2.05, 2.55, 2.0 ... %, 2.0 and 2.25% by weight.

[0076] The first alkoxysilane can be a tetra-alkoxysilane, a poly(tetra-alkoxysilane), or a mixture thereof. The tetra-alkoxysilane has the formula (R a O) 4Si, wherein each R a are organic groups which may be the same or different, and each R ais preferably an alkyl group having 1 to 22 carbon atoms, more preferably 1 to 10 carbon atoms, including 2, 3, 4, 5, 6, 7, 8, and 9 carbon atoms, including methyl, ethyl, and propyl. An example is tetraethoxysilane (TEOS). Poly(tetra-alkoxysilane) is an oligomer of one or more tetra-alkoxysilanes formed by partial hydrolysis. Preferably, poly(tetra-alkoxysilane) contains 2 to 14 monomer units, more preferably 4 to 10 monomer units, including 5, 6, 7, 8, and 9.

[0077] The first alkoxysilane may contain a silica moiety. A silica moiety is a Si(O)4 group that is bonded to four atoms, [OSi(O2)] n O, where n is 2 to 14, more preferably 4 to 10, including 5, 6, 7, 8 and 9.

[0078] The organoalkoxysilane is selected from the group consisting of mono-organoalkoxysilanes, bi-organoalkoxysilanes, tri-organoalkoxysilanes, and mixtures thereof. The organoalkoxysilane is represented by the formula R 1 n Si(OR b ) 4-n where n is 1, 2 or 3. 1 R is an organic group such as alkyl (e.g., linear alkyl, branched alkyl, cyclic alkyl, glycidoxyalkyl, methane chloroxyalkyl, and aminoalkyl), aryl, vinyl, and heteroaryl. 1 Examples of R include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, and octadecyl. 1 Each R contains 1 to 22 carbon atoms, more preferably 1 to 10 carbon atoms, including 2, 3, 4, 5, 6, 7, 8, and 9 carbon atoms. bare organic groups which may be the same or different, and each R b is preferably an alkyl group having 1 to 22 carbon atoms, more preferably 1 to 10 carbon atoms, including 2, 3, 4, 5, 6, 7, 8, and 9 carbon atoms, including methyl, ethyl, and propyl. An example of an organoalkoxysilane is triethoxyoctylsilane.

[0079] The organoalkoxysilane may contain an organooxysilane moiety. The organooxysilane moiety may be R 1 n Si(O) (4-n) / 2 R is a group, where n is an integer of 1, 2, or 3. 1 R is an organic group such as alkyl (e.g., linear alkyl, branched alkyl, cyclic alkyl, glycidoxyalkyl, methane chloroxyalkyl, and aminoalkyl), aryl, vinyl, and heteroaryl. 1 Examples of R include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, and octadecyl. Preferably, R contains 1 to 22 carbon atoms, more preferably 1 to 10 carbon atoms, including 2, 3, 4, 5, 6, 7, 8, and 9 carbon atoms. An example of an organooxysilane moiety is octylsilane.

[0080] The second alkoxysilane is selected from the group consisting of poly(dialkyl)siloxanes, and mixtures thereof. The poly(dialkyl)siloxane is preferably represented by the formula R c O(R 2 2SiO) n (SiR 2 2) OR c In the formula, n is an integer from 2 to 14, preferably from 4 to 10, including 5, 6, 7, 8, and 9. 2 is an organic group such as methyl, ethyl, or phenyl, and each R c is an end blocking group such as alkyl, including methyl, ethyl, and propyl, which form an alkyloxy group, or H, which forms a hydroxyl group. Both hydroxy and alkyloxy groups are reactive groups. 2 It is also possible for the groups to be hydroxyl and / or alkyloxy groups. 2 and R c each independently preferably contains 1 to 22 carbon atoms, more preferably 1 to 10 carbon atoms, including 2, 3, 4, 5, 6, 7, 8, and 9 carbon atoms. Preferably, the poly(dialkyl)siloxane is polydimethylsiloxane or polydiethylsiloxane. Preferably, the poly(dialkyl)siloxane has a weight average molecular weight of 200 to 10,000, more preferably 500 to 5,000.

[0081] The second alkoxysilane may contain a poly(dialkyl)siloxane moiety. The poly(dialkyl)siloxane moiety is an O(R 2 2SiO) n (SiR 2 2) O or O(R 2 2SiO) n (SiR 2 2) OR c group, where n is an integer from 2 to 14, preferably from 4 to 10, including 5, 6, 7, 8, and 9. 2 are independently an organic group such as methyl, ethyl, or phenyl, and each R c is an end blocking group such as alkyl, including methyl, ethyl, and propyl, to form an alkyloxy group, or H to form a hydroxyl group; both hydroxy and alkyloxy groups are reactive groups. 2 It is also possible for the groups to be hydroxyl and / or alkyloxy groups. 2 and R c preferably each independently contain 1 to 22 carbon atoms, more preferably 1 to 10 carbon atoms, including 2, 3, 4, 5, 6, 7, 8, and 9 carbon atoms. Preferably, the poly(dialkyl)siloxane moieties are polydimethylsiloxane moieties or polydiethylsiloxane moieties.

[0082] Typically, the particles and the three components of the composition are thoroughly mixed together and then placed in a sealed container. The container is then evacuated and heated to a temperature at which at least two components become vapor. The temperature is maintained for a time sufficient to allow polymerization and the formation of a coating on the particles, preferably with continuous mixing during the polymerization process. Carrying out the polymerization reaction for a longer duration allows for a more complete coating of the particle surface. The container is then flooded with an inert gas flow that allows for the removal of volatile by-products such as alcohol, and is then cooled to room temperature. The formed polymer coating contains three respective silane moieties: (1) a silica moiety, (2) an organooxysilane moiety selected from the group consisting of a mono-organooxysilane moiety, a bi-organooxysilane moiety, and a tri-organooxysilane moiety, and (3) a poly(dialkyl)siloxane moiety.

[0083] Preferably, the polymerization temperature is from 80° C. to 120° C., more preferably from 90° C. to 110° C., including 92, 94, 96, 98, 100, 102, 104, 106, and 108° C. Preferably, the amount of time for polymerization is from 0.5 to 10 hours, more preferably from 1 to 6 hours, including 2, 3, 4, and 5 hours.

[0084] After the polymerization process, the coated powder is heated to 120°C to evaporate any volatile compounds. This drying removes very little weight. For the purpose of determining the amount of silicon in the coating in SiO2 equivalent, the coated powder is heated to a temperature of 600°C to 800°C. This process can be carried out in a thermogravimetric device or other device. Rapid oxidation in air to either 600°C or 800°C converts all silicon-containing moieties in the coated powder to SiO2. The composition of the ignited powder can be confirmed by various assay methods.

[0085] A variety of techniques can be used to analyze the coated powders of the present invention: the inorganic oxide particles can be dissolved in various acids to determine the relative amounts of polymer and inorganic oxide, and the remaining polymer coating can then be examined using Fourier Transform Infrared Spectroscopy (FTIR) to determine the presence of different moieties and the relative amounts of each moiety. Mass spectrometry, thermogravimetric analysis (TGA), or inductively coupled plasma Other techniques such as spectroscopy (ICP, Inductively Coupled Plasma Spectroscopy) are also used. Relative monomer unit ratios can be established by using standards of known composition.

[0086] The coated powder may also be analyzed by solid state NMR; 13 C and 29 The Si NMR signal can be examined to determine the presence of different moieties and the relative amounts of each moiety. Additionally, the inorganic oxide particles can be dissolved in various acids and the remaining polymer coating analyzed by NMR. 13 C and 29 The Si NMR signal can be examined to determine the presence of different moieties and the relative amounts of each moiety. Standards of known composition can be used to establish a baseline.

[0087] The coated powders may be examined for properties using photostability tests, chemical reactivity tests and hydrophobicity tests. The coated powders are super photostability if in the TiO2 photostability test, the coated powders have a photostability of ΔE of 15 or less, preferably ΔE=1-14, including ΔE=2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 and 13. The coated powders are super photostability if in the DPPH photostability test, the coated powders have a photostability of ΔE of 4.5 or less, preferably ΔE=1-4, including ΔE=4.0, 3.5, 3.0, 2.5, 2.0, 1.5 and 1.0. The coated powders are super photostability if in the effect pigment photostability test, the coated powders have a photostability of ΔE of 1.15 or less, preferably ΔE=0.5-1.0, including 1.05, 0.95, 0.85, 0.75, 0.65 and 0.55. Preferably, the coating powder has a chemical reactivity of ΔE=0-20, more preferably ΔE=0-17, and most preferably ΔE=0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 16. Preferably, the coating powder is hydrophobic or slightly hydrophobic, most preferably hydrophobic.

[0088] The coated powders may be used to form dispersions with non-polar liquids, preferably cosmetic oils such as capric / caprylic triglycerides, linear alkyl benzoates, ethylhexyl benzoate, natural oils, and silicone oils. Preferably, the dispersions contain at least 40% by weight of the coated powder (solids), more preferably at least 50% by weight of the coated powder (solids), including at least 55% by weight of the coated powder (solids), at least 60% by weight of the coated powder (solids), and at least 65% by weight of the coated powder (solids), such as 50-65% by weight of the coated powder (solids), and 55-60% by weight of the coated powder (solids). Such dispersions may be prepared by a variety of conventional mixing processes, including mixing using rotor-stator machines, planetary mixing, high pressure homogenizers, ultrasonic mixing, and media milling. Additional emulsifiers or dispersants may be included in the dispersion. Examples include trisodium phosphate (Hostaphat KW 340 D; Clariant) at 5-15% by weight solids. (manufactured by

[0089] Surprisingly, the high solids dispersions of the coating powders have a relatively low viscosity. Preferably, the viscosity is at most 60,000 cP, more preferably at most 30,000 cP, and most preferably at most 6,000 cP. Examples include viscosities of 1,000 to 50,000 cP, and 5,000 to 30,000 cP.

[0090] A preferred embodiment of the present invention includes the addition of an antioxidant to the dispersion containing the coated powder. The antioxidant is oxidized when exposed to UV radiation, resulting in a loss of antioxidant power. In addition, zinc oxide and other metal oxides are photoreactive and generate free radicals upon exposure to UV radiation. Metal oxides, in combination with antioxidants, have a greater loss of AP than the antioxidant alone. However, by combining the coated powder with the antioxidant, the relative AP value of the dispersion remains higher than the relative AP value of the antioxidant alone. The composition of the coated powder and the antioxidant together exhibit a synergistic effect, since the coated powder is ultra-photostable. The antioxidant is effective because the UV radiation is blocked or absorbed by the particles, preserving the AP value. could be.

[0091] The dispersion may contain one or more antioxidants, including but not limited to vitamins, antioxidant minerals, antioxidant proteins, antioxidant enzymes and coenzymes, phytonutrients, antioxidant hormones, mycosporine-like amino acids (MAA), and algae-derived antioxidants. The antioxidants may include antioxidants derived from vitamins A, B, C, D, E, E. The antioxidants may be water-soluble, fat-soluble, or fat-soluble and water-soluble. Suitable vitamins include vitamin A (including retinoids and carotenoids), vitamin C (ascorbic acid), vitamin E (tocopherol), and vitamin K. Suitable retinoids include retinol, retinoic acid (tretinoin), retinal, and retinyl palmitate. Suitable minerals include copper, manganese, iodide, and zinc. Suitable enzymes and coenzymes include melatonin, superoxide dismutase, catalase, and glutathione peroxidase. Suitable phytonutrients include carotenoids, flavonoids, phenolic acids, and non-flavonoid phenolic acids. Suitable carotenoids include alpha-carotene, retinol, astaxanthin, beta-carotene, canthaxanthin, lutein, lycopene, and zeaxanthin. Suitable flavonoids include hindered phenols, apigenin, luteolin, tangeretin, isohamnetin, kaempferol, and the like. Suitable phenolic acids include phenol, polyphenol, alkylated phenol, and hindered phenol. Suitable phenols include butylated hydroxyanisole, butylated hydroxytoluene, cannabinoids, capsaicin, carvacrol, cresol, estradiol, eugenol, gallic acid, guaiacol, thymol, tyrosine, and sesamol. Gallic acids include salts and esters of gallic acid, also known as gallates. Suitable non-flavonoid phenolic acids include curcumin, flavonolignans, xanthones, and eugenol. Suitable mycosporine-like amino acids (MAAs) include mono-substituted MAAs such as mycosporine-glycine and mycosporine-taurine, di-substituted MAAs such as parithenic acid and shinorine, and derivatized MAAs such as parithine-threonine sulfate and parithine-threonine glycoside. Examples of suitable MAAs are described in (Wada et al., Mycosporine-Like Amino Acids and Their Derivatives as Natural Antioxidants. Antioxidants 2015, 4, 603-646). The antioxidants involved include ascorbate, glutathione, phlorotannin, equol, extronol, prenyltoluquinone, tetraprenyltoluquinol, sargothunbergol A, fucodiphloretol, terpenoids, phycocyanin, These include phycocyanobilin, fucoxanthin, phlorotannin, and lutein. Other possible organic antioxidants include bilirubin, citric acid, oxalic acid, phytic acid, n-acetylcysteine, uric acid, green tea, hydroxy-trilosol, dihydro-quercetin, ubiquinone, glutathione, alpha-lipoic acid, folic acid, ellagic acid, caffeic acid, and phytoestrogens. The above antioxidants also include any salt, ester, or acid form of the antioxidant.

[0092] The dispersion may contain one or more phyto-extracts. A "phyto-extract" is a substance obtained from a plant. The phyto-extract preferably imparts color. The phyto-extract must be compatible with non-aqueous compositions; stable in air; non-staining to skin; non-irritating to skin at the dosage; and non-toxic at the dosage. The phyto-extract has a purity level of at least 95%. Examples of suitable phyto-extracts include curcumin, lycopene, beta-carotene, lutein, zeaxanthin, meso-zeaxanthin, and anthocyanins. Sources of curcumin include turmeric. Lycopene Sources of lutein include beets, cherries, goji berries, pink grapefruit, pomegranates, raspberries, red cabbage, red onions, strawberries, tomatoes, and watermelon. Sources of beta-carotene include apricots, cantaloupe, carrots, oranges, papayas, peaches, persimmons, pumpkins, cucumbers, sweet potatoes, winter squash, and yams. Sources of lutein, zeaxanthin, and meso-zeaxanthin include avocados, broccoli, Brussels sprouts, cabbage, green beans, leafy greens, orange peppers, and thyme. Sources of anthocyanins include peas, spinach, yellow corn, and zucchini. Sources of anthocyanins include beets, blackcurrants, blueberries, cherries, eggplants, figs, grapes, plums, prunes, red cabbage, and red currants. Phyto-extracts can be chemically modified by hydrolysis, hydrogenation, esterification, or saponification. When a phyto-extract that normally imparts color is chemically modified, it may no longer impart color. For example, curcumin imparts a yellow color, but hydrogenated tetra-hydrocurcumin is colorless.

[0093] The dispersion may contain one or more plant bioextracts. A "plant bioextract" is a natural extract of a plant that provides fragrance and may also provide color. The plant bioextract must be compatible with non-aqueous compositions; stable in air; non-staining to skin; non-irritating to skin at the dosage; and non-toxic at the dosage. Synthetic versions of plant bioextracts are outside the scope of the term "plant bioextract". Examples of suitable plant bioextracts include arnica extract (Arnica montana), basil extract (Ocimum basilicum), boswellia extract (Boswellia sacra), calendula extract (Calendula officinalis), cambogia extract (Camellia officinalis ... Momile extract (Roman chamomile (Anthemis nobilis)), cinnamon oil (Cinnamomum verum), clove oil (Syzygium aromaticum), coptis japonica Extract (Coptis aspleniifolia), Echinacea Extract (Echinacea purpurea), Eucalyptus Oil (Eucalyptus occidentalis), Ginger Root Extract (Zingiber officinale). officinale), Grape seed extract (Vitis vineficaule) (Vitis vinefera), Green Tea Extract (Camellia sinensis), Guggul Resin Extract (Commiphora wightii), Horse Chestnut Fruit Extract (Aesculus hippocastanum), Japanese Knotweed Extract (Polygonum cuspidatum), Licorice Extract (Glycyrrhiza glabra), Neem Leaf Extract (Azadirachta indica), Olive Fruit and Leaf Extract (Olea europaea), Papaya Extract (Carica papaya), Balsam of Peru (Myroxylon balsamum), pineapple extract (Ananas comosus), pomegranate extract (Punica granatum L.), rosemary extract (Rosmarinus officinalis), sage extract (Salvia officinalis), sandalwood extract (Santalum album), turmeric extract (Curcuma longa) and witch hazel extract (Hamamelis japonica). All the above examples may include different species of the same genus of plants. For example The witch hazel extract can be obtained from Hamamelis japonica, Hamamelis ovalis, Hamamelis mollis or Hamamelis virginiana.

[0094] The composition may include a phyto-extract. The phyto-extract may be selected to impart color. Phyto-extracts that do not impart color may also be included in the composition. The phyto-extract must be compatible with non-aqueous compositions; stable in air; non-staining to skin; non-irritating to skin in the amounts used; and non-toxic in the amounts used. The phyto-extract has a purity level of at least 95%. Examples of suitable phyto-extracts include curcumin, lysine, riboflavin, linoleic acid ... These include copene, beta-carotene, lutein, zeaxanthin, meso-zeaxanthin, and anthocyanins. Sources of curcumin include turmeric. Sources of lycopene include beets, cherries, goji berries, pink grapefruit, pomegranates, raspberries, red cabbage, red onions, strawberries, tomatoes, and watermelon. Sources of beta-carotene include apricots, cantaloupe, carrots, oranges, papayas, peaches, persimmons, pumpkins, cucumbers, sweet potatoes, winter squash, and yams. Sources of lutein, zeaxanthin, and meso-zeaxanthin include avocados, broccoli, Brussels sprouts, cabbage, green beans, leafy greens, orange peppers, peas, spinach, yellow corn, and zucchini. Sources of anthocyanins include beets, blackcurrants, blueberries, cherries, eggplants, figs, grapes, plums, prunes, red cabbage, and red currants. Phyto-extracts may be chemically modified by hydrolysis, hydrogenation, esterification, or saponification. Phyto-extracts that normally impart color, such as curcumin, may no longer impart color if chemically modified, such as tetra-hydrocurcumin. The composition may contain 0.01% to 5.0% phyto-extract, preferably 0.01% to 1.0% phyto-extract, including 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19% and 0.20% phyto-extract.

[0095] The composition may include a plant bio-extract. The plant bio-extract may provide fragrance and may also impart color. The plant bio-extract must be compatible with non-aqueous compositions, such as lipophilic or hydrophobic; stable in air; non-staining to skin; non-irritating to skin at the dosage; and non-toxic at the dosage. Examples of suitable plant bio-extracts include arnica extract (Arnica montana), basil extract (Ocimum basilicum), boswellia extract (Boswellia sacra), calendula extract (Calendula officinalis), chamomile extract (Anthemis nobilis), cinnamon oil (Cinnamon zeylanicum), clove oil (Clove oleracea), coptis extract (Coptis asplenifolia), echinacea extract (Echinacea purpurea), eucalyptus oil (Eucalyptus occidentalis), ginger root extract (Zingiber officinale), grape seed extract (Vitis vinifera), and the like. vineyard (Vinefera), green tea extract (Camellia sinensis), guggul resin extract (Commiphora wichii), horse chestnut extract (Aesculus hippocastanum), Japanese knotweed extract (Polygonum cuspidatum), licorice extract (Glycyrrhiza glabra), neem leaf extract (Azadirachta indiaca), olive fruit and leaf extract (Olive), papaya extract (Papaya sativa), balsam of Peru (Myloxylon balsam), pineapple extract (Ananas comosus), pomegranate extract (Punica granatum) L.), rosemary extract (Rosmarinus officinalis), sage extract (Salvia officinalis), sandalwood extract (Santalum album), turmeric extract (Curcuma longa) and witch hazel extract (Hamamelis japonica). The dispersion may also include an extract from an algae species.These species include Hijikia fusiformis, Spirulina platensis, Aphanizomenon, Spirulina maxima, Sargassum kjellamanianum, S. siliquastrum, Rhodomela confervoides, Symphjocladia latiuscula, Kappaphycus alvarezzi, Botryococcus braunii, Dunaliella salina, Cystoseira crinita, and others. crinite, Ecklonia stolonifera, Sargassum thunbergii, S. thunbergii, and Ecklonia cava. The composition may contain 0.10% to 10.0% plant bio-extract, preferably 2.0% to 6.0% plant bio-extract, including 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, and 4.0% plant bio-extract.

[0096] The composition may contain an oil-soluble antioxidant. If present, the antioxidant is different from the phyto-extract. Examples of suitable antioxidants include carotene, catechin, lycopene, resveratrol, vitamin E or vitamin A. "Vitamin E" may refer to any tocopherol or tocotrienol compound that constitutes the vitamin E family of compounds, such as alpha-tocopherol and gamma-tocotrienol. The compositions may contain 0.01% to 5.0% antioxidant, preferably 0.1% to 3.0% antioxidant, including 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% and 2.0% antioxidant.

[0097] The dispersion may contain one or more protist extracts. A "protist extract" is a material obtained from a protist. Protists include eukaryotic organisms that are not animals, plants or fungi. The protist extract is preferably a material that is rich in astaxanthin. Examples of suitable protist extracts include plankton extracts and algae extracts, particularly red algae extracts.

[0098] The dispersion may contain a protist extract. The protist extract is preferably a substance rich in astaxanthin. Examples of suitable protist extracts include plankton extracts and algae extracts, in particular red algae extracts. The dispersion may contain 0.01% to 5.0% protist extract, preferably 0.1% to 3.0% protist extract, including 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% and 2.0% protist extract. Cosmetic and dermatological preparations may contain cosmetic ingredients, auxiliaries and / or additives, such as co-emulsifiers, fats and waxes, stabilizers, thickeners, bioactive ingredients, film-forming agents, fragrances, dyes, pearlizing agents, preservatives, pigments, electrolytes, and pH regulators. Suitable co-emulsifiers are preferably the known W / O and also O / W emulsifiers, such as polyglycerol esters, sorbitan esters or partially esterified glycerides. Typical examples of fats are glycerides; waxes, such as beeswax, paraffin wax or microcrystalline waxes, possibly in combination with hydrophilic waxes. Stabilizers include metal salts of fatty acids, such as magnesium stearate, aluminum stearate and / or zinc stearate. Examples of thickeners include cross-linked polyacrylic acid and its derivatives, xanthan gum, guar gum, agar, alginates and tylose, polysaccharides such as carboxymethylcellulose and hydroxyethylcellulose, as well as fatty alcohols, monoglycerides and fatty acids, polyacrylates, polyvinyl alcohols and polyvinylpyrrolidones. Bioactive ingredients include plant extracts, protein hydrolysates and vitamin complexes. Conventional film-forming agents include hydrocolloids such as chitosan, microcrystalline chitosan or quaternized chitosan, polyvinylpyrrolidone, vinylpyrrolidone / vinyl acetate copolymers, acrylic acid-based polymers, and quaternary cellulose derivatives. Examples of preservatives include parabens, diazolidinyl urea, iodopropynyl butylcarbamate, and sorbic acid.Examples of pearlizing agents include glycol distearate esters, such as ethylene glycol distearate, fatty acids and fatty acid monoglycol esters. Pigments that may be used are suitable and approved materials for cosmetic purposes. Antioxidants such as amino acids, retinol, flavonoids, polyphenols, vitamin C and tocopherol may also be included.

[0099] Cosmetic and dermatological preparations may be in the form of solutions, dispersions or emulsions; for example, sun protection preparations may be in the form of water-in-oil creams, oil-in-water creams and lotions, aerosols, and the like. The compositions may be in the form of liquids, pastes or solids, as foaming creams, gels, greases, marking pencils, powders, sprays or alcohol-water lotions. Solvents for these compositions include water; oils and fats such as triglycerides of capric or caprylic acid, as well as castor oil; fats, waxes and other natural and synthetic fatty substances, for example esters of fatty acids with alcohols of low carbon numbers, such as isopropanol, propylene glycol or glycerin, or esters of fatty alcohols with alkanoic acids of low carbon numbers or with fatty acids; alcohols, diols or polyols of low carbon numbers and their ethers, preferably ethanol, isopropanol, propylene glycol, glycerin, ethylene glycol, ethylene glycol monoethyl or monobutyl ether, propylene glycol monomethyl, monoethyl or monobutyl ether, diethylene glycol monomethyl or monoethyl ether. Other examples include isopropyl myristate, isopropyl palmitate, isopropyl stearate, isopropyl oleate, n-butyl stearate, diisopropyl adipate, n-hexyl laurate, n-decyl oleate, glyceryl stearate, isooctyl stearate, isononyl stearate, isononyl isononanoate, 2-ethylhexyl palmitate, 2-ethylhexyl laurate, 2-hexyldecyl stearate, 2-octyldodecyl palmitate, oleyl oleate, oleyl erucate, erucyl oleate, and erucyl erucate.

[0100] The cosmetic and dermatological preparations may be in the form of a solid stick and may contain natural or synthetic waxes, fatty alcohols or fatty acid esters, liquid fats such as paraffin oil, castor oil, isopropyl myristate, semi-solid components such as yellow petrolatum, lanolin, solid components such as beeswax, ceresin and fine crystalline waxes, and odorifera wax, and high melting waxes including carnauba wax and candelilla wax.

[0101] The cosmetic preparations may be in the form of a gel, preferably comprising water, organic thickeners such as gum arabic, xanthan gum, sodium alginate, cellulose derivatives such as methylcellulose, hydroxymethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, and inorganic thickeners such as aluminium silicates such as bentonite, or mixtures of polyethylene glycol and polyethylene glycol stearate or polyethylene glycol distearate.

[0102] The coating powders and dispersions may also be included in paints, sealants and other coatings, which may also contain binders such as polyacrylates, polyurethanes, polyalkyds, polyepoxides, polysiloxanes, polyacrylonitriles and / or polyesters. Organic solvents may also be present, including ethanol, butyl acetate, ethyl acetate, acetone, butanol, alkanes, methanol, propanol, and pentanol; ethers / acetals such as tetrahydrofuran and 1,4-dioxane; ketones such as diacetone alcohol and methyl ethyl ketone; and polyhydric alcohol derivatives such as ethylene glycol, propylene glycol, and diethylene glycol, or mixtures thereof. These compositions are suitable for use in coatings on wood, polyvinyl chloride (PVC), plastics, steel, aluminum, zinc, copper, medium density fiberboard (MDF), glass and concrete. Depending on which coating powder is included, the composition can provide a coating on the substrate that can be clear, UV resistant, and / or provide greater scratch resistance.

[0103] The coating powders and dispersions can be blended with resins to provide organic polymer composites. Examples of resins include polyethylene, polypropylene, polystyrene, polyethylene terephthalate, acrylonitrile styrene (AS) resins, acrylonitrile Butadiene styrene (ABS, acrylonitrile butadiene styrene) resin, acrylonitrile Examples of the resins that can be used include acrylonitrile ethylene styrene (AES) resins, polyvinylidene chloride, methacrylic resins, polyvinyl chloride, polyamides, polycarbonates, polyaryl esters, polyimides, polyacetals, polyether ketones, polyether sulfones, polyphenylene oxides, and polyphenylene sulfides, as well as mixtures thereof. In these compositions, additives such as colorants, fluorescent agents, antioxidants, anti-aging agents, UV absorbers, lubricants, antistatic agents, surfactants, fillers (coating powders and dispersions can also act as fillers), plasticizers, stabilizers, foaming agents, expanding agents, electrically conductive powders, electrically conductive short fibers, deodorants, softeners, thickeners, viscosity reducers, diluents, water repellents, oil repellents, crosslinking agents, and hardeners may also be present. These organic polymer compositions can be molded by a variety of techniques, including injection molding, blow molding, extrusion, calendar molding, flow molding, compression molding, meltblowing, and spunbonding, to produce shaped articles such as fibers, threads, films, sheets, tapes, and injection molded articles, as well as molded bodies such as hollow fibers, pipes, and bottles. Alternatively, the compositions can be subjected to secondary molding methods commonly applied to thermoplastics, such as vacuum forming, air pressure forming, and lamination molding. [Example]

[0104] The photostability tests for TiO2, DPPH and effect pigments are customized tests. Different colorimeter photostability tests are designed to provide a high level of sensitivity for various materials. Each material has a different absorption band and reactivity, so different tests are required to accurately measure the resulting color change upon UV radiation exposure. For example, TiO2 is very reactive with DPPH, so typically TiO2 is not tested using DPPH. The three colorimeter tests can be performed quickly and easily by comparing the color change in the sample to a standard. The test results can be verified by using other test methods such as electron spin resonance (ESR) spectroscopy. EXAMPLES

[0105] The improved photostability of the coated powders can be measured using the TiO2 photostability test described above. In this test, the passing condition is a ΔE of 15 or less, based on experience with selected antioxidants and spectrophotometric testing involving an ESR-based method. The data in Table 1 below are based on a constant 40m 2 / g (35 nm) rutile phase TiO2 particles. Coating surface coverage is based on surface area, so the mass fraction of the coating components should be determined according to the specific surface area of ​​the base particle. Response modeling suggests that pass / fail criteria are violated when A+B exceeds 2.5% for the following cases: In this case, a typical base particle is 40m 2 / g, the pass / fail boundary is m for all particle types. 2 / g, which is expressed as 0.0625%. As shown in Table 1 below, all compositions meeting the criteria have a ΔE of 15 or less.

[0106] [Table 1]

[0107] Because the coating is composed only of cross-linked polymer residues, the coating components are expressed as weight percent of each part of the total powder (inorganic substrate plus coating) as opposed to reactant amounts. Because not all of the component material reacts with the particle surface, it is more accurate to measure the weight percent of SiO2 available from each part in the coating after ignition. EXAMPLES

[0108] W / O formulations containing a physical UV filter (150 nm zinc oxide) were analyzed for the amount of UV-induced free radicals using the following radical potential (RP) method: was used and analyzed.

[0109] The metastable spin probe PCA (2,2,5,5-tetramethylpyrrolidine N-oxyl) is added to the product under test, the sample is inserted into a capillary quartz tube, and the concentration of the spin marker is monitored by ESR spectroscopy before and after a defined UV irradiation. The PCA spin probe is photostable and resistant to antioxidants, but reacts instantly with UV-generated free radicals in the sample (mainly lipid peroxides and lipid radicals). The amount of UV-generated free radicals can be quantitatively detected from a calibration curve.

[0110] Materials and Methods A water / EtOH solution of the spin trap (PCA) was added to the W / O emulsion to obtain a final concentration of 0.01 mM PCA. The sample was inserted into an ESR capillary quartz tube (40 μL) before starting the ESR measurement and UV irradiation.

[0111] UV irradiation of the samples was performed using a 300 W Oriel UV solar simulator (Newport). The irradiance as an integral value over the spectral range was E(UVB=280-320)=23.5 W / m 2 and E (UVA = 320-400 nm) = 180 W / m 2The irradiation time was varied to test the effect of different UV doses. The radiation intensity was controlled before each measurement. The measurements were performed using a commercially available highly sensitive X-band benchtop Electron Spin Resonance Spectrometer MiniScopeMS300 (Magnettech GmbH, Berlin, Germany). did.

[0112] Results and Discussion The amount of UV-induced free radicals in the cosmetic formulations was measured. By knowing the concentration of spin-trap PCA in the sample (0.01 mM), the amount of PCA reduced can be calculated. Since one electron is required to reduce one molecule of PCA, the radical concentration in the sample can be calculated using the calibration curve. The percentage of induced free radicals corresponding to each product is shown in Table 2.

[0113] [Table 2]

[0114] Two different coating techniques for the coating of ZnO were tested. With respect to the uncoated material, no protective effect was observed in the sample with the coating formed from octyltriethoxysilane. Conversely, the radical formation was reduced to less than 3% in the sample containing ZnO with the multifunctional coating. The percentage change in induced free radicals for the different products when the UV exposure time is changed is shown in Figure 1. The materials and monomers used to form the components of the multifunctional coating are shown in Table 3 below.

[0115] [Table 3] EXAMPLES

[0116] In the presented experimental design, antioxidants of different photolabile properties were added to ZnO-containing formulations using different coating techniques. The antioxidant activity of these formulations was determined using the AP method before and after UV irradiation of the formulations.

[0117] The antioxidants were selected according to the following criteria: (1) the antioxidants used were suitable for use in cosmetic formulations, and (2) the five raw materials represented different classes of antioxidants with different molecular mechanisms, hydrophilic and lipophilic characteristics. The final concentration of each antioxidant was selected based on the antioxidant capacity of the raw materials. All concentrations were within the range of recommended use based on EU guidelines. Entered the enclosure.

[0118] Antioxidants become oxidized when exposed to UV radiation, resulting in a decrease in antioxidant power (AP). Table 4 below shows that AP is decreased upon exposure to UV radiation. Information in the "Post-UV" column was collected 10 minutes after exposure to UV radiation, which corresponds to 2.4 MED (minimal erythermal doses). While antioxidants reduce the number of free radicals, exposure to UV radiation significantly reduces the AP of antioxidants.

[0119] [Table 4]

[0120] Materials and Methods The antioxidant capacity and reactivity measurements were carried out by using ESR spectroscopy. This spectroscopic technique is particularly suitable for the analysis of antioxidants in cosmetic products, since it is capable of quantifying free radicals and is applicable to opaque, viscous and colored samples. The measurements were carried out using an X-band ESR spectrometer, Microscope MS 300 (Magnettech, Germany) and the following technical parameters: 60 G sweep width, 100 gain, 1 G modulation amplitude, 7 mW attenuation, 3365 G central field, 0.14 s time constant. Antioxidant power (AP) is a parameter that allows to quantify both the reactivity and the speed of an antioxidant. Test radical DPPH (2,2-diphenyl-1-picryl-hydrazyl, Sigma-Aldrich, Munich, Germany) is used as the detection molecule. At least three concentrations of test samples are prepared and added to DPPH to obtain an initial radical concentration of 0.1 mM. The signal intensity decay of each test sample concentration is recorded at different time intervals during the reaction until saturation is reached and all antioxidant active molecules have reacted with the test radicals.

[0121] From these intensities, first-order kinetics were obtained for each concentration pair. The reaction time (t r ) and the characteristic weight (w c ) using static parameters.

[0122] For a direct comparison of different antioxidants, the AP method was applied to the activity of vitamin C (ascorbic acid, obtained from Sigma-Aldrich, Munich, Germany, at the highest grade of purity). Standardize. The antioxidant activity of a 1 ppm vitamin C solution is defined as an antioxidant unit (AU). For each formulation, the AP value was determined before and after exposure to UV radiation.

[0123] result 300 mg of each formulation was applied onto a glass plate (microscope slide) and illuminated for 10 min (22.7 J / cm) using a solar simulator (Honle SOL 2 solar simulator). 2 ), U The slides were exposed to UV radiation. The products were collected from the slides and the AP was determined. The sample weights before and after UV exposure were controlled for each sample. Weight loss due to water evaporation was less than 5% for all samples.

[0124] The formulation containing ZnO showed a protective effect during relatively low UV irradiation, independent of the coating. Therefore, the product containing 10% ZnO was diluted 4 times with a placebo. The following experiments were therefore carried out with the formulation containing 2.5% ZnO. The formulation containing 2.5% ZnO showed a photoprotective effect against most of the antioxidants used, due to the UV scattering effect.

[0125] Nevertheless, there are significant differences between the two ZnO preparations: the antioxidants were less stable in the formulation containing ZnO with a coating formed from octyltriethoxysilane compared to ZnO with a multifunctional coating.

[0126] The generation of UV-induced free radicals was evaluated for the two ZnO-containing formulations (see Example 2 above). The particles with the multifunctional coating did not show radical generation, while high photocatalytic activity was observed for the formulation containing ZnO with a coating formed from octyltriethoxysilane. This photocatalytic activity results in the generation of hydroperoxides, mainly hydroxyl radicals, which react immediately with the antioxidants, leading to oxidation and subsequent AP reduction. Figure 2 shows that the relative AP value after UV irradiation is greater for the multifunctional coating than for the coating formed from octyltriethoxysilane. Data showing that the relative AP value after UV irradiation is greater for the multifunctional coating than for the coating formed from octyltriethoxysilane can be seen in Table 5.

[0127] [Table 5] JPEG0007649568000017.jpg48170 EXAMPLES

[0128] This example illustrates a coated nanocrystalline TiO2 powder. The coated powder is coated powder (i) from Table 1. The coated powder contains, in terms of weight percentage, 92.7% TiO2 from the propylsilane portion, 4.7% SiO2, 0.149% SiO2 from the silicate portion, and 2.5% SiO2 from the polydimethylsiloxane. The ΔE of this sample was 14.4 based on photostability testing. By using assays such as X-ray fluorescence (XRF), inductively coupled plasma spectroscopy (ICP), etc., it is possible to determine the weight percentage of each component of the ignited powder. The ratio of the formula weights of the reactants and the formula weight of SiO2 can be used to calculate the weight lost during ignition. EXAMPLES

[0129] (virtuality) This example illustrates coated nanocrystalline ZnO powder. Nanocrystalline ZnO (specific surface area = 17 m 2 / g, corresponding average particle size=63 nm) are coated with propylsilane moieties, silicate moieties, and polydimethylsiloxane moieties. ZnO particles are coated with the moieties in the same relative proportions as in Example 4. The mixture is homogenized for 30 seconds and then transferred to a glass container, which is then sealed. The sealed container is then transferred to an oven and heated to a temperature of 100-110° C. and held for 1.5 hours. The resulting coated powder is then dried by opening the container and placing it back in the same oven and holding it at a temperature of 100-110° C. for 1.5 hours. The resulting coated powder is highly hydrophobic and ultra-photostable. The coated powders of this example and the corresponding dispersions are suitable for use in cosmetic sun protection formulations. EXAMPLES

[0130] (virtuality) This example illustrates a high solids dispersion of a coating powder suitable for addition to cosmetic formulations. 460 g of ethylhexyl benzoate (Finsolv® EB; Innospec) and 4 0 g of emulsifier is placed in a jacketed steel vessel maintained at a constant temperature of 30°C. The emulsifier trisealeth-4 phosphate (Hostaphat KW 340 D; Clariant) is a waxy solid, anionic O / W emulsifier designed to be used in formulations requiring a certain level of viscosity, such as cream preparations. The contents of the vessel are premixed using a Coles-type sawtooth high shear impeller under gentle mixing conditions for 5 minutes until the mixture is homogenous. In the configuration used in this example, the impeller blade diameter is 1 / 3 of the vessel diameter and is positioned 1 blade diameter from the bottom of the vessel. 500 g of the coated TiO2 powder of Example 4 is added to the liquid contents under gentle mixing until all the powder is wetted. The mixer speed is then increased to 2500 rpm for 15 minutes. The resulting dispersion is pourable. EXAMPLES

[0131] (virtuality) This example illustrates a water-in-oil emulsion cosmetic sun protection formulation containing only inorganic UV sunscreens: The following oil phase ingredients are added to a heated container and mixed at low intensity at 80° C. until clear:

[0132] [Table 6]

[0133] The oil phase mixture is then cooled to 60° C. and mixed with the coated TiO powder of Example 4 (12.0 parts by weight), followed by passing through a high shear mixer until the mixture is homogenous. The mixture is then cooled to 45° C.

[0134] Combine the following aqueous phase ingredients in a separate container:

[0135] [Table 7]

[0136] The homogenized oil phase mixture and water phase mixture are mixed until a homogenous emulsion is formed. Note that any fragrance (0.2 parts by weight) may be replaced with an equivalent amount of deionized water. EXAMPLES

[0137] (virtuality) This example illustrates a composition comprising the coating powder of Example 5 and an antioxidant such as hydroxytyrosol. 0.05% hydroxytyrosol is combined with 2.5% ZnO. This composition maintains a greater level of AP because the coating powder blocks the antioxidant from being oxidized by UV radiation while the antioxidant increases the photostability of the composition. EXAMPLES

[0138] (virtuality) This example illustrates a composition comprising the coating powder of Example 4 and tocopherol. The composition maintains a greater level of AP because the coating powder blocks the antioxidant from being oxidized by UV radiation while the antioxidant increases the photostability of the composition. EXAMPLES

[0139] (virtuality) This example illustrates one example of a UV curable coating composition of the present invention. Mix the following ingredients until homogeneous:

[0140] [Table 8]

[0141] The compositions of this example can be applied to a substrate as a wet film using a wound wire rod or a spray gun and subsequently cured using UV radiation to provide a UV protective hard coating. EXAMPLES

[0142] This example illustrates a composition comprising an effect pigment. Effect pigments are typically platelet or plate-like pigment particles coated with a thin layer of a secondary material having a higher refractive index. The composition of the underlying platelets is typically mica, synthetic mica, silica, or alumina. The coating is typically titanium dioxide (typically in anatase form), iron oxide, and bismuth oxychloride.

[0143] [Table 9]

[0144] The tests were carried out at a concentration of 0.125% by weight of effect pigment in a 0.125% by weight solution of DPPH in butoxyethanol. The samples were subjected to a 0.35 W / m 2 UVA radiation for 20 minutes. Each sample was prepared in 4 replicates. D-50 is measured in micrometers. In Table 9, ΔE is significant if the t-test is 1.53 or greater.

[0145] [Table 10]

[0146] (References) European Patent No. 0761774 British Patent No. 785,393 British Patent No. 825,404 US Patent Publication No. 20060167138 US Patent Publication No. 20060210495 U.S. Pat. No. 3,024,126 U.S. Pat. No. 3,562,153 U.S. Pat. No. 3,647,742 U.S. Pat. No. 3,649,588 U.S. Pat. No. 3,920,865 U.S. Pat. No. 3,948,676 U.S. Pat. No. 4,061,503 U.S. Pat. No. 4,061,503 U.S. Pat. No. 4,068,024 U.S. Pat. No. 4,141,751 U.S. Pat. No. 4,233,366 U.S. Pat. No. 4,454,288 U.S. Pat. No. 4,644,077 U.S. Pat. No. 4,882,225 U.S. Pat. No. 5,277,888 U.S. Pat. No. 5,486,631 U.S. Pat. No. 5,536,492 U.S. Pat. No. 5,562,897 U.S. Pat. No. 5,565,591 U.S. Pat. No. 5,607,994 U.S. Patent No. 5,631,310 U.S. Pat. No. 5,718,907 U.S. Pat. No. 5,756,788 U.S. Patent No. 5,843,525 U.S. Pat. No. 5,959,004 U.S. Pat. No. 5,993,967 U.S. Patent No. 6,022,404 U.S. Patent No. 6,045,650 U.S. Patent No. 6,086,668 U.S. Patent No. 6,214,106 U.S. Patent No. 6,500,415 U.S. Patent No. 7,182,938 U.S. Patent No. 7,438,836 International Publication No. 2009 / 131910 Brochure International Publication No. 95 / 23192 Brochure Jung K, Richter J, Kabrodt K, LuckeIM, Schellenberg I, Herrling T. Theantioxidativepower AP--A new quantitative time dependent (2D) parameter forthedetermination of the antioxidant capacity and reactivity of differentplants. Spectrochim Acta A Mol Biomol Spectrosc. 63(2006):846-50 Jung K, Sacher M, Blume G, Jansen F, Herrling T. HowActive are BiocosmeticIngredients? SOFW-Journal 133 1 / 2 - 2007 Andersch Bjorkman Y(1), Hagvall L, Siwmark C, Niklasson B, Karlberg AT, BraredChristensson J. Air-oxidized linalool elicits eczema inallergic patients - arepeated open application test study. Contact Dermatitis.2014 Mar;70(3):129-38 Jung K, Heinrich U, Tronnier H, Schnyder M, Herzog B,Herrling Th. High levelsof free radicals in suncare products induce Acne Aestivalisin sensitive subjects.SOFW / 142 (2016): 2-8 Wlaschek M et al. Solar UV irradiation and dermalphotoaging. J Photochem PhotobiolB.2001 Oct;63(1-3):41-51 Wada et al., Mycosporine-Like Amino Acids and TheirDerivatives as NaturalAntioxidants. Antioxidants 2015, 4, 603-646 Varahalaroa Vadlapudi,Antioxidant activities of marine algae: A review.Medicinal Plants asAntioxidant Agents: Understanding Their Mechanism of Actionand TherapeuticEfficacy, 2012: 189-203 ISBN: 978-81-308-0509-2

Claims

1. (a) particles; (b)(1) a silica portion; (2) an organooxysilane moiety selected from the group consisting of a mono-organooxysilane moiety, a bi-organooxysilane moiety, and a tri-organooxysilane moiety; and (3) Poly(dialkyl)siloxane portion a coating on a surface of the particle comprising: A coating powder comprising the organooxysilane portion and the silica portion, 2 The amount by weight of the corresponding amount is m of the specific surface area of ​​the particles to be coated. 2 / g of the total weight of the coating powder, and the particles have an average particle size of 10 to 500 nm; The coating powder, wherein the particles comprise at least one oxide selected from the group consisting of ZnO, TiO2, and mixtures thereof.

2. (1) The coating powder according to claim 1, and (2) Fluid A dispersion comprising: 0.1 seconds at 25°C -1 ~100 seconds -1 and / or has a viscosity of up to 50,000 cP when measured at a shear rate in the range of 0.1 s at 25° C. -1 ~100 seconds -1 and / or has a viscosity of at most 10,000 cP when measured at shear rates in the range The dispersion further comprises a dispersing aid and / or the dispersing aid is selected from the group consisting of stearic acid, stearates, palmitic acid, palmitate, oleic acid, oleate, polyhydroxystearic acid, phosphate esters, linear alkyl substituted amines, triglycerol esters, polyethylene glycerol esters, and mixtures thereof.

3. The dispersion described in claim 2, further containing an antioxidant.

4. A water-in-oil or oil-in-water emulsion comprising a coating powder according to claim 1 and a liquid carrier, the liquid carrier being preferably cosmetically acceptable; and / or the liquid carrier comprises a member selected from the group consisting of alkyl benzoates, fatty acid esters, naturally occurring oils, silicone oils, and mixtures thereof; and / or The water-in-oil or oil-in-water emulsion, wherein the liquid carrier comprises a member selected from the group consisting of ethyl benzoate, linear alkyl benzoates, capric / caprylic triglycerides, and mixtures thereof.

5. A composition comprising the coating powder of claim 1, The composition is a cosmetic composition.

6. A composition comprising the coating powder of claim 1, comprising an antioxidant.

7. A composition according to claim 5 or 6, a dispersion according to claim 2 or 3, or an emulsion according to claim 4 for use in the following method: a method for protecting the skin from light comprising covering the skin with said composition, dispersion or emulsion; a method of protecting keratinous materials comprising coating the keratinous materials with said composition, dispersion or emulsion; A method of protecting human skin comprising coating the skin with said composition, dispersion or emulsion; or A method for inhibiting lipid peroxidation comprising applying the composition, dispersion, or emulsion to the skin.

8. A composition according to claim 5 or 6, a dispersion according to claim 2 or 3, or an emulsion according to claim 4 for use in the following method: a method of preventing or reducing the formation of fine lines and wrinkles on the skin comprising covering the skin with said composition, dispersion or emulsion; A method for preventing loss of skin elasticity comprising coating the skin with said composition, dispersion or emulsion; or A method of preventing skin thinning comprising covering the skin with said composition, dispersion or emulsion.

9. A method for producing a coating powder, comprising the steps of: (i) particles; (ii) a first alkoxysilane, which becomes the silica portion, selected from the group consisting of tetra-alkoxysilanes, poly(tetra-alkoxysilanes), and mixtures thereof; (iii) an organoalkoxysilane selected from the group consisting of mono-organoalkoxysilanes, bi-organoalkoxysilanes, tri-organoalkoxysilanes, and mixtures thereof; and (iv) a second alkoxysilane selected from the group consisting of poly(dialkyl)siloxanes and mixtures thereof. coating the particles with a polymer by polymerizing a composition comprising The organooxysilane portion and the silica portion, SiO 2 The amount by weight of the corresponding amount is m of the specific surface area of ​​the particles to be coated. 2 / g of the total weight of the coating powder, and the particles have an average particle size of 10 to 500 nm; The process as described above, wherein the particles comprise at least one oxide selected from the group consisting of ZnO, TiO 2 and mixtures thereof.

10. A method for producing the coating powder according to claim 9, comprising the steps of: Each organooxysilane moiety is represented by the formula R 1 n SiO ((4-n)/2) (Wherein, n=1, 2 or 3, and each R 1 The groups are independently selected from the group consisting of alkyl, alkenyl, alkynyl, aryl and heterocyclic radicals, and / or each R 1 The groups have 1 to 18 carbon atoms and are independently selected from the group consisting of alkyl, alkenyl, and aryl, and / or each R 1 The groups are independently selected from the group consisting of alkyl, aryl, vinyl, glycidoxyalkyl, methacryloxyalkyl, aminoalkyl, and mercaptoalkyl; Each poly(dialkyl)siloxane moiety has the formula O(R 2 2 SiO) n (SiR 2 2 )O or O(R 2 2 SiO) n (SiR 2 2 ) OR c (wherein n is an integer from 2 to 14, and each R 2 The group is alkyl, R c is selected from the group consisting of H, methyl, ethyl and propyl, and / or the organooxysilane contains a propylsilane moiety and the poly(dialkyl)siloxane comprises polydimethylsiloxane; and / or The poly(dialkyl)siloxane has the formula R c O (R 2 2 SiO) n (SiR 2 2 ) OR c (In the formula, m is an integer from 2 to 14, and each R 2 The group is an alkyl group, and each R c The group is an alkyl group or H), and / or the poly(dialkyl)siloxane is polydimethylsiloxane or polydiethylsiloxane, and / or the poly(dialkyl)siloxane is linear.

Citation Information

Patent Citations

  • Silicone-treated powder and composition containing the same

    JP1997053023A

  • Siloxane star-grafted polymers, ceramic powders coated therewith, and methods of preparing coated ceramic powders

    JP2000508684A

  • Organopolysiloxane powder-treating agent, powder treated by the same treating agent, and cosmetic containing the same powder

    JP2007238645A

  • Metallic effect pigments comprising mixed inorganic / organic layers, methods for producing such metallic effect pigments and their use

    JP2009503207A

  • Multifunctional coated powders and high solids dispersions

    US9139737B1